2014
DOI: 10.1007/s10802-014-9929-y
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Examining the Effects of Aerobic Physical Activity on Attention-Deficit/Hyperactivity Disorder Symptoms in Young Children

Abstract: The goal of this study was to compare the effects of before school physical activity (PA) and sedentary classroom-based (SC) interventions on the symptoms, behavior, moodiness and peer functioning of young children (Mage = 6.83) at risk for attention-deficit/hyperactivity disorder (ADHD-risk; n = 94) and typically developing children (TD; n = 108). Children were randomly assigned to either PA or SC and participated in the assigned intervention 31 minutes per day, each school day, over the course of 12 weeks. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 40 publications
4
55
0
12
Order By: Relevance
“…However, there was no intervention effect on several other parental-and teacher-reported measures (Hoza et al 2015). In the crossover trial, a significantly lower percentage of on-task behaviour was observed in the sedentary control versus the 10-min exercise break condition but not the 5-or 20-min condition (Howie et al 2014).…”
Section: Behavioural Conduct/pro-social Behaviourmentioning
confidence: 77%
“…However, there was no intervention effect on several other parental-and teacher-reported measures (Hoza et al 2015). In the crossover trial, a significantly lower percentage of on-task behaviour was observed in the sedentary control versus the 10-min exercise break condition but not the 5-or 20-min condition (Howie et al 2014).…”
Section: Behavioural Conduct/pro-social Behaviourmentioning
confidence: 77%
“…Por un lado, siete artículos incluyeron escolares diagnosticados TDAH (Choi et al, 2015;Hoza et al, 2015;Huang et al, 2014;Pan et al, 2015;Smith et al, 2013;Verret et al, 2012;Ziereis & Jansen, 2015). Por otro lado, seis artículos trabajaron con escolares TEA (Dickinson & Place, 2014;Hillier et al, 2011;Nicholson et al, 2011;Oriel et al, 2011;Pan et al, 2016;Vander & Sprong, 2011).…”
Section: Resultsunclassified
“…Las sesiones de AF consistieron en la realización de ejercicio aeróbico como carrera (Nicholson et al, 2011;Oriel et al, 2011;Vander & Sprong, 2011), práctica deportiva como natación (Huang et al, 2014) o tenis de mesa (Pan et al, 2015), AF combinada con relajación (Hillier et al, 2011) u otro tipo de sesiones a intensidad moderada o moderada-vigorosa (Choi et al, 2015;Hoza et al, 2015;Smith et al, 2013;Verret et al, 2012) a destacar el trabajo de habilidades motrices (Ziereis & Jansen, 2015) o utilización de videojuegos activos (Dickinson & Place, 2014). Antes y después de realizar el programa de intervención fueron medidas las variables propias del RA y RC.…”
Section: Resultsunclassified
See 2 more Smart Citations